Targeted long-read sequencing analysis and antifungal susceptibility profiles of Sporothrix schenckii isolates from Thailand. - Nattapong Langsiri; Wijit Banlunara; Oranong Klaychontee; Navaporn Worasilchai; Regielly Cognialli; Flavio de Queiroz-Telles; Bram Spruijtenburg; Theun de Groot; Eelco F J Meijer; Ariya Chindamporn (PLoS Neglected Tropical Diseases, 2025)
Sporothrix spp. are dimorphic fungi capable of undergoing morphological changes in response to temperature variations. The genus Sporothrix includes the species S. schenckii sensu stricto, S. brasiliensis, S. globosa, and S. luriei that cause sporotrichosis, which can range from local skin infections to systemic infections in immunocompromised individuals. As these species are morphologically similar, molecular techniques that utilize barcoding genes are required for accurate identification. While the Internal Transcribed Spacer (ITS) region is the universal fungal barcode, the calmodulin gene offers higher resolution for phylogenetic classification of Sporothrix using Sanger sequencing. This study evaluated the ability of long-read nanopore sequencing of calmodulin and ITS to identify species level and allow phylogenetic analysis of Sporothrix strains isolated from humans and felines in Thailand. We found that the calmodulin sequencing with Oxford Nanopore Technology (ONT) consistently classified all isolates as S. schenckii sensu stricto, whereas the ITS region showed a lower discriminatory power, complicating species identification in some isolates. The phylogenetic analysis of the calmodulin region indicated that all isolates localized in a specific S. schenckii sensu stricto subclade together with other isolates from Southeast Asia, while the three residual S. schenckii subclades were associated with other geographical locations. Antifungal susceptibility testing on all Sporothrix strains demonstrated elevated in vitro minimum inhibitory concentrations (MICs) to itraconazole for 8 out of 26 isolates. Altogether, this study demonstrated that ONT sequencing of calmodulin allows accurate species identification and phylogenetic analysis of S. schenckii sensu stricto isolates from Thailand, of which some also demonstrated elevated MIC values for itraconazole.